The role of refinancing in the interest rate pass-through to fixed-rate mortgage contracts - Jonas Ladegaard Hensch (Danmarks Nationalbank, 2021)
In this paper, I study how mortgage refinancing influences the interest rate pass-through to household budgets via fixed-rate mortgage contracts in Denmark. I develop a model based on a state-dependent process of household actions that endogenously determines household refinancing decisions as a function of their incentives. I show that the model leads to a dynamic equilibrium, in which all households with positive incentives respond (over a period of adjustment) to monetary policy. The dynamic equilibrium formalizes the interest rate pass-through into an analytical expression, which I use to assess the empirical relevance of the model and the contribution of the refinancing channel in that context. I estimate the aggregate response via a cointegrated VAR model in the period 2008-2020, and complement the results with detailed mortgage data at individual household level. I document that the long-run interest rate pass-through is significantly below unity in the years after the financial crisis and subsequently converges towards a level close to unity. I argue that the result is driven by a structural shift in refinancing incentives in the years after the financial crisis. The result can be used to understand the importance of asymmetric effects in the refinancing channel of monetary policy transmission.
Keywords: E43; E44; E52; G40; G50; 330; Fixed-rate mortgages; Inaction; Interest rate pass-through; Monetary transmission; Refinancing